Neurosurgical Meningitis: Clinico-Microbiological Profile and Treatment Outcome from a Tertiary Care Center in India - Ravikant Porwal; Abdul Ghafur; Vidyalakshmi P. R.; Priyadarshini Kannaian; Pradeepa Arivazhaghan (Indian Journal of Neurosurgery, 2015)
Abstract